The Effect of Pandanus conoideus Lamk Extract to the Serum Level of TNF-α, IL-10 and Parasitemia of Plasmodium berghei Infected in Mice - Zeth Robeth Felle; Mahardika Agus Wijayanti; Supargiyono Supargiyono (Tropical Medicine Journal, 2013)
ABSTRACT Introduction: Study on the effects of red fruit (Pandanusconoideus Lamk) has been conducted with various result.Objectives: In this study, the effect of red fruit extract on the level of cytokines TNF-α, IL-10 and the parasitemia of Plasmodium berghei infected Swiss mice were evaluated.Methods: Quasi-experimental design with pre and post test only control group was applied. Sixty male Swiss mice of 8 weeks old and weighs 20-30 g, was simply randomized into four treatment groups. Group I (K1) was stimulated with the extract for 2 weeks before and 2 weeks after infection with P.berghei. K2 was stimulated with the extract for 2 weeks before infection, K3 was stimulated with the extract for 2 weeks after infection and K4, negative control, was given 0.6% tween 40. The dose of the extract was 7.8 mg/30g mice BW, intra gastric once a day. Serum level of TNF-α and IL-10 was measured by ELISA Sandwich methods and the number of parasitemia were examined microscopically. The difference level of TNF-α, IL-10 and parasitemia of each treatment group were analyzed by t-test, one way anova, honestly significant different (HSD) and multivariate analysis (manova).Results: There were significan cedifferences of parasitemia in K3 group compared to others. Parasitemia on day-3 was 18.464% and reduced to 1.054% on day-9. Parasitemia of K2 group was 13.204% on day-3 and 32.455% on day-9. Parasitemia of negative control group was 27.304% on day-3 and 78.506% on day-9. The TNF-α level of K3 group decreased along with the infection, it was 26.985 pg/Ml on day-0 and 22.244 pg/mL on day-6. The IL-10 level increased at all groups and the highest level was on K3 group.Conclusion: Effect of red fruit extract on P.berghei infected mice was reduced both parasitemia and TNF-α level but increased of IL-10 level.Keywords : Pandanus conoideus Lamk, Malaria, Parasitemia, TNF-α, IL-1